Teacher Self-Efficacy as a Determinant of Performance: An Empirical Study of Private Vocational High School Teachers in Bogor Regency - Awaludin, Awaludin; Setyaningsih, Sri; Hidayat, Rais (IJORER : International Journal of Recent Educational Research, 2026)
Purpose: This study analyzes the influence of teacher self-efficacy on teacher performance and the mediating role of organizational trust among teachers at Private Vocational High Schools (SMK) in Bogor Regency, Indonesia. Method: This quantitative study used path analysis on a sample of 175 permanent foundation teachers at Private Vocational High Schools in Bogor Regency. Data were collected using measured instruments to assess self-efficacy (24 items), teacher performance (36 items), and trust (20 items) on a 5-point Likert scale. Path analysis and the Sobel test were used to analyze both direct and indirect effects. Results: The study found a significant positive direct effect of self-efficacy on teacher performance (β = 0.151, p < 0.05). In addition, self-efficacy positively influenced organizational trust (β = 0.190, p < 0.05), which in turn affected teacher performance (β = 0.325, p < 0.05). An indirect effect of self-efficacy on teacher performance through trust was also found (β = 0.062, p < 0.05), indicating that trust serves as an important mediating mechanism. Novelty: This study expands understanding of the psychological factors influencing teacher performance in the context of vocational education in Indonesia by demonstrating the mediating role of organizational trust in the relationship between self-efficacy and performance outcomes. The findings provide practical implications for school leaders in developing teacher competencies through strategies that enhance self-efficacy and foster organizational trust.